Pembuatan dan Implementasi Website Desa Merangin - Sumaiyah Sumaiyah; Egi Dwi Irawan; Angga Yudha Wibowo; Radha Khairani; Tuti Alawiyah; Indriyani Saputri; Salviyah Elmiati; Jalden Darma Putra Armeza; Umi Ratna Sari; Amelia Sekar Ayu Pramesti; Farah Erikha Putri; Agung Tresna Hermawan; Walidul Khair El-Ilya; Latifa Hanum (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
In the current digital era, village websites function as an important means of connecting village governments with their communities via the internet. Its main function is to provide an information platform that is easily accessible to village residents, where they can find village profiles that contain a lot of information about the village. The methods used are data collection, website creation, admin training, carrying out website processes online, and analyzing the usability and sustainability of the website. The village profile website is the online face of a village which contains various information regarding history, government structure, vision and mission and so on. The Merangin Village profile website can be accessed at the domain desamerangin.id. The evaluation results show that this website has clarified village government and made it easier for people to get information